Evolution of deforestation and environmental liabilities in an agrarian reform settlement project in Southeast Para (Research, Society and Development, 2020)
Currently, the Agrarian Reform Settlement Projects in the Southeast of Pará are the focus of discussions on the loss of forest cover in the Amazon, as they are among the areas that most contribute to the deforestation process. In this sense, this work aimed to evaluate the evolution of deforestation and environmental liabilities in the São Francisco Settlement Project, in the city of Eldorado do Carajás, in a time span that runs from 1990 to 2020, identifying the main processes that lead to the loss of forest cover at the place of study. For this, the work was based and supported by landscape analysis methods, namely geotechnologies, adopting the same concepts worked by PRODES that measures clear cut deforestation polygons. In general, there was a significant increase in deforestation at the study site, which lost approximately 5,000 hectares of vegetation. In general terms, this rate represents more than 60% of forest lost and converted to other uses. Currently, at the legal reserve level, the environmental liability reaches more than 20% of the total area and in relation to APP's there was also a reduction of over 20% in riparian vegetation, which implies the loss of important environmental services provided by these locations. Thus, it can be seen that without the use of adequate agricultural technology and technical assistance to small producers, there is no long-term sustainability of the means of production and natural resources, requiring production alternatives that combine the use of already open areas, generating employment and income.